Analisis Hadis tentang Larangan Pernikahan Semarga dalam Tradisi Batak Toba di Kota Sibolga - Simanjuntak, Irwan Syahputra; Sulidar, Sulidar (Journal of Islamic Thought and Philosophy, 2026)
This study examines hadiths related to the prohibition of same-clan (semarga) marriage in the Batak Toba tradition in the city of Sibolga, with a focus on the relationship between Islamic teachings and customary norms that are still maintained today. Previous studies generally discuss the prohibition of same-clan marriage from either the perspective of customary law or Islamic law separately; therefore, there have been limited studies that analyze the contextual meaning of hadiths within the social practices of Muslim Batak Toba communities. This research offers novelty by analyzing the relationship between hadith interpretation, local cultural values, and socio-religious practices in a multicultural society. The method used is qualitative research with a field study approach and a normative hadith analysis. Data were collected through semi-structured interviews with five informants consisting of customary leaders, Islamic scholars, and local community members, supported by observation and documentation. The data analysis was conducted through data reduction, data presentation, and conclusion drawing using a descriptive-analytical approach. The findings show that the prohibition of same-clan marriage is understood not merely as a religious ruling, but also as a form of respect for the kinship system and cultural identity. However, hadiths related to the selection of a spouse are interpreted flexibly, allowing customary law and Islamic teachings to coexist harmoniously without causing conflict within the community.